2019
DOI: 10.24953/turkjped.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Nasal nitric oxide levels in primary ciliary dyskinesia, cystic fibrosis and healthy children

Abstract: Primary ciliary dyskinesia (PCD) is a rare, inherited disorder characterized by recurrent respiratory tract infections. The measurement of nasal nitric oxide (nNO) is an important test for the diagnosis of PCD. In this study, we aim to evaluate NIOX-MINO Ò , which is an easily applicable method for measuring nNO, in the diagnosis of patients with PCD and define diagnostic cut-off levels. Furthermore, determining the normal limits of nNO in healthy children and investigating nNO levels of children with cystic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Altered RNS has been reported in PCD. Nasal NO (nNO) measurement is recommended as the initial test in patients with clinical suspicion of PCD since diminished nNO values are characteristic of patients with PCD [172]. However, despite its good sensitivity, there are cases of PCD with normal values of nNO, so even if the nNO is normal-if the symptoms are consistent-the disease should not be ruled out [173,174].…”
Section: Primary Ciliary Dyskinesia and Oxidative Stressmentioning
confidence: 99%
“…Altered RNS has been reported in PCD. Nasal NO (nNO) measurement is recommended as the initial test in patients with clinical suspicion of PCD since diminished nNO values are characteristic of patients with PCD [172]. However, despite its good sensitivity, there are cases of PCD with normal values of nNO, so even if the nNO is normal-if the symptoms are consistent-the disease should not be ruled out [173,174].…”
Section: Primary Ciliary Dyskinesia and Oxidative Stressmentioning
confidence: 99%
“…They observed that the mean nNO values were 10.4 ± 8.3 ppb, 22.8 ± 18.7 ppb, and 21 ± 8.9 ppb, respectively. Notably, nNO levels in children with PCD were found to be significantly lower than those in children with CF and the healthy control group (p < 0.05) [52].…”
Section: Nno In Cystic Fibrosismentioning
confidence: 78%
“…While NO concentration in airways is usually high in chronic inflammatory diseases (allergic rhinitis, bronchiectasis, etc.) because of the induction of NO synthase by inflammatory cytokines such as TNF-a, IL-1b, and interferon-c [48], cystic fibrosis (CF) represents an exception since CF patients usually have normal or even reduced nNO levels [49] (Table 1).…”
Section: Applications Of Nno In Other Respiratory Inflammatory Diseasesmentioning
confidence: 99%